Occurrence of Cyprinus carpio (Linnaeus, 1758) in a World Biosphere Reserve, the Mar Chiquita Coastal Lagoon (Argentina) - González Castro, Mariano (2015)
Paleogeographical, morphological, ecological, physiological, linguistic, archeological and historical evidence demonstrated that the wild ancestor of the common carp Cyprinus carpio Linnaeus, 1758 originated in the Black, Caspian and Aral sea drainages and naturally dispersed east into Siberia and China and west as far as the Danube River (Balon, 1995). This species has been introduced in all continents (Lever, 1996). In most countries where it was introduced, a wide array of negative impacts on native biota and ecosystems has been documented (Bernstein and Olson, 2001). Because of its historical use in aquaculture and as an ornamental fish, this species has become widely dispersed. It is recorded in more than 50 localities in Argentina: in the Paran a, Uruguay and Plata river basins (Liotta, 2014), as well as in the Mirim lagoon (Rio Grande do Sul, Brazil) (Garcia et al., 2004). In the Pampa plain the distribution of this species is restricted to freshwater ecosystems of the Salado River Basin (Rosso, 2006).